KLASIFIKASI ILMU PENGETAHUAN DALAM PERSPEKTIF JĀBIR BIN ḤAYYĀN - Asep N. Musadad (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
The central purpose of this article is to provide a preliminary exploration on epistemological background of the classical Islamic sciences through the investigation on the classification of knowledge. One of the earliest exponent to turn to this problem is Jābir bin Ḥayyān (Geber) (721 - 815 AD), known as the Father of Arabic and – indirectly – Latin Alchemy. Start on describing Jābir’s profile and his significance in Islamic philosophy, this article discusses the classification of knowledge according to him in his book “Kitāb al-Ḥudūd” (Book of Limits), in which he make his own classification of various knowledge. It finally deals with the philosophical basis of the classification and the intellectual perspective of its author.